Modelagem e controle de um conversor CC-CC sepic isolado de interruptor único com célula dobradora de tensão na saída para aplicação em microinversor fotovoltaico - Muhongo, Milton Luis Filipe (2023)
This dissertation presents a study of an isolated DC-DC converter model for interfacing or coupling via a DC bus with a DC-AC converter in a microinverter. The proposed structure initially uses the already known sepic DC-DC converter model, but techniques are used to achieve a greater gain in the use of advantages that the conventional topology cannot provide. The topology achieved is the result of joining two isolated sepic DC-DC converters, the junction is made in such a way that the structure achieved uses only a single switch and a voltage doubler cell is incorporated at the output of both in order to allow the converter to have the capacity to establish a high voltage gain with a low duty cycle and low transformation ratio for the coupled inductor. The topology is designed to operate as the DC-DC block of a microinverter for systems of up to 500W. The sepic DC-DC converter proposed in this dissertation is modeled and a compensator is sequentially designed to control the input voltage. The control operates in conjunction with a maximum power tracking algorithm (MPPT) of the P&O type, through which a voltage reference is provided to allow the control to act and consequently generate the duty cycle signal. To validate the approaches, a prototype 500 W converter was designed, built and subjected to numerous laboratory tests, with the static gain, waveforms, control and efficiency being experimentally evaluated, the latter reaching a maximum value of 95%. As a result, it can be concluded that despite the satisfactory results, it can be seen that a more appropriate construction of the component design could result in the mitigation of certain problems and possibly improve the efficiency of the system.